2020
DOI: 10.1021/acs.langmuir.9b03852
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic Transport of a Charged Dye in a Freely Suspended Liquid Film: Experiments and Numerical Simulations

Abstract: Electrokinetic transport of a charged dye within a free liquid film stabilized by a cationic surfactant, trimethyl-(tetradecyl)ammonium bromide, subjected to an external electric field was investigated. Confocal laser scanning microscopy was used to visualize fluorescein isothiocyanate (FITC) separation within the stabilized liquid film. Numerical simulations were performed using the finite element method to model the dynamics of charged dye separation fronts observed in the experiments. Because of the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…The effects of the liquid–solid boundary are probed by changing the material of construction (solid) from glass to acrylic, which decreased the liquid–solid zeta potential, as shown in Table 3 . Furthermore, it is expected that increasing the electric field strength will increase the body force exerted on the EDL, according to eq 7 : 21 where F ivf is the body force, E is the electric field, c i is the concentration of species i within the solution, and z i is the electric charge of species i . Stronger electric fields will induce greater electroosmotic flow, accelerating the movement of fluid close to the interfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of the liquid–solid boundary are probed by changing the material of construction (solid) from glass to acrylic, which decreased the liquid–solid zeta potential, as shown in Table 3 . Furthermore, it is expected that increasing the electric field strength will increase the body force exerted on the EDL, according to eq 7 : 21 where F ivf is the body force, E is the electric field, c i is the concentration of species i within the solution, and z i is the electric charge of species i . Stronger electric fields will induce greater electroosmotic flow, accelerating the movement of fluid close to the interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical double layer thickness was estimated to be in the range of 1.51 to 8.81 nm and negligible compared to the full scale of the model. The presence of the EDL was considered through slip velocity as in refs ( 21 )( 33 ), and ( 34 ). The electrical charge of the surfactant-covered interfaces is balanced by counterions from the bulk solution, so the net charge at the interfaces was taken to be zero.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When an external electric field is applied to a foam, three main effects can be expected. First, a pH gradient starts to form as electrochemical reactions occur at the electrodes . This will lead to acidic conditions at the anode (bottom electrode), and alkaline conditions at the cathode (top electrode).…”
Section: Resultsmentioning
confidence: 99%
“…EOF will also affect the motion of analytes in an electrophoretic separation system and depending on its strength and direction relative to the electrophoretic mobility of each analyte, it may help or hinder the separation. , It is important to consider the effects of EOFs generated in liquid foams for different surfactant types on potential electrophoretic separations as well as on the stability and lifetime of the foam. The effect of EOF on freely suspended surfactant-laden films has been investigated by several researchers, and the effects on the stability of liquid foams have been previously investigated. , While electrophoresis in a free liquid film has been investigated by, separation of charged molecules inside a three-dimensional liquid foam has not been demonstrated. In our previous work, it was shown that the foam stability depends on the surfactant type and the strength of the electric field applied; therefore, it is interesting to know whether the required separation can be achieved before the foam starts to collapse.…”
Section: Introductionmentioning
confidence: 99%